Face coverings in post-COVID society to help prevent the transmission of respiratory illnesses on public transit - Fitzgerald, Brendan; BCIT School of Health Sciences, Environmental Health; Chen, Dale (BCIT Environmental Public Health Journal, 2022)
During the COVID-19 pandemic, cases of influenza drastically decreased in numerous countries around the world. Several non-pharmaceutical health measures were put in place to help mitigate the spread of the virus, including a mask mandate for public spaces. On public transit, there is potential for respiratory virus spread through droplet transmission and common contact fomites between riders. This study investigated how current residents of Metro Vancouver who use transit at least once per week would support optional guidelines for mask-use during annual flu seasons to help continue to mitigate the transmission of respiratory illnesses after COVID-19 mandates have ended.